2019
DOI: 10.1080/2162402x.2019.1593802
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1β provided by KIT-competent mast cells is required for KRAS-mutant lung adenocarcinoma

Abstract: Mast cells (MC) have been identified in human lung adenocarcinoma (LADC) tissues, but their functional role has not been investigated in vivo. For this, we applied three mouse models of KRAS-mutant LADC to two different MC-deficient mouse strains (cKit Wsh and Cpa3.Cre). Moreover, we derived MC gene signatures from murine bone marrow-derived MC and used them to interrogate five human cohorts of LADC patients. Tumor-free cKit Wsh and Cpa3.Cre mice were deficient in alveolar and skin KITdependent (KIT+) MC, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…Two external cohorts confirmed this conclusion. The differences and controversial conclusions in different studies (Baram et al , 2001; Kurebayashi et al , 2016; Lilis et al , 2019) may be due to the mixture of activated and resting mast cells. The function of activated mast cells may be masked by the resting mast cells.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Two external cohorts confirmed this conclusion. The differences and controversial conclusions in different studies (Baram et al , 2001; Kurebayashi et al , 2016; Lilis et al , 2019) may be due to the mixture of activated and resting mast cells. The function of activated mast cells may be masked by the resting mast cells.…”
Section: Discussionmentioning
confidence: 97%
“…One study revealed that mast cells correlated with angiogenesis and poor outcome in stage I LUAD (Baram et al , 2001). Another study has revealed KIT‐competent mast cells fuel KRAS‐mutant LUAD formation, growth and metastasis by providing interleukin‐1β and are associated with LUAD progression (Lilis et al , 2019). However, one research indicated that only mast cells were found by univariate analysis to be associated with better prognosis in LUAD (Kurebayashi et al , 2016).…”
Section: Discussionmentioning
confidence: 99%
“…84 Mast cells could facilitate growth and metastasis by generating IL-1β in LUAD progression. 85 Conversely, certain studies revealed that greater abundance of mast cells was related to better prognosis and prolonged survival in early-stage LUAD cases. 54,86 We also found relatively enhanced expression of CD4 and CD8A indicative of a strengthened immune response in the low-risk group.…”
Section: Discussionmentioning
confidence: 99%
“…Infiltration of MCs has also been reported in human lung adenocarcinoma (LADC) tissues. Lilis and coworkers applied three KRAS-mutant LADC models to two MC-deficient mouse strains (cKitWsh and Cpa3.Cre) [50]. Acts through CGRPR and induces serotonin release [67] They showed that MCs infiltrate into tumors and that a MC deficiency protects the mice from tumor initiation within the airway and alveolar epithelium following induction with the carcinogen urethane or the oncogenic KRASG12D mutant respectively.…”
Section: Role Of Mcs In Lung Cancermentioning
confidence: 99%
“…Acts through CGRPR and induces serotonin release [67] They showed that MCs infiltrate into tumors and that a MC deficiency protects the mice from tumor initiation within the airway and alveolar epithelium following induction with the carcinogen urethane or the oncogenic KRASG12D mutant respectively. Enhanced tumor progression required IL-1β release from KIT+ MCs localized within the TME [50].…”
Section: Role Of Mcs In Lung Cancermentioning
confidence: 99%